308 High-Resolution Magnetic Resonance Imaging Findings Following Trigeminal Rhizotomy. (August 2016) - Goodwin, C. Rory; Northcutt, Benjamin; Seeburg, Daniel; Shin, Jaehoon; Theodros, Debebe; Abu-Bonsrah, Nancy A.; Herzka, Daniel; Aygun, Nafi; Blitz, Ari M.; Lim, Michael
Abstract : INTRODUCTION: Patients with trigeminal neuralgia often undergo glycerol or radiofrequency-thermocoagulation glycerol rhizotomy of the trigeminal nerve for treatment of symptoms. To date, radiological changes in patients with trigeminal neuralgia postrhizotomy have not been described. The aim of this study was to evaluate patients after trigeminal rhizotomy to characterize postrhizotomy changes on 3D high-resolution MRI. METHODS: A retrospective review of trigeminal neuralgia protocol studies was performed on 26 postrhizotomy patients compared with 54 treatment-naive trigeminal neuralgia subjects. Examinations were reviewed independently by 2 neuroradiologists blinded to side of symptoms and treatment history. Symmetry of Meckel caves on constructive interference in steady state (CISS) and the presence of contrast enhancement within the trigeminal nerves on volumetric interpolated breath-hold examination (VIBE) images was assessed subjectively. Signal intensity (SI) of Meckel cave was measured on coronal noncontrast CISS imaging on each side. RESULTS: Postrhizotomy changes include subjective clumping of nerve roots and/or decreased CISS SI within Meckel cave, which was identified in 17 of 26 (65%) patients after rhizotomy and 3 of 54 (6%) treatment-naive patients ( P < .001). CISS SI within Meckel cave was on average 13% lower on the side of rhizotomy in posttreatment patients, compared with 1% difference in controls ( P < .001). Small regions of temporal encephalomalacia were noted in 8 of 26 cases (31%) of patient postrhizotomy and 0 of 54 (0%) of treatment-naive patients ( P < .001). CONCLUSION: Post-trigeminal rhizotomy findings frequently include nerve clumping and decreased CISS signal in Meckel cave. Small areas of temporal encephalomalacia are encountered less frequently.